Distribution, host range and detection of seed-borne yellow mosaic disease on yardlong beans (Vigna unguiculata subsp. sesquipedalis L.) in the special region of Yogyakarta, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mulyadi D, Sulandari S, Hartono S, Somowiyarjo S. 2021. Distribution, host range and detection of seed-borne yellow mosaic disease on yardlong beans (Vigna unguiculata subsp. sesquipedalis L.) in the special region of Yogyakarta, Indonesia. Biodiversitas 22: 3949-3957. Yellow mosaic disease found in legumes is caused by Mungbean yellow mosaic India virus (MYMIV). MYMIV has been reported to cause yellow mosaic infection on yardlong beans (Vigna unguiculata subsp. Sesquipedalis L.) in various regions of Indonesia and has resulted in major yield loss. Symptoms of mosaic and yellowing are found in the leaves and on the pods, which means that the virus may be seed-borne. The purpose of this study was to identify the distribution, host range of pathogens, and to investigate whether yellow mosaic virus was seed-borne or not. Sample collection, disease incidence and severity observations were done at yardlong bean fields in the District of Sleman, Bantul, and Kulon Progo. Samples were tested using PCR (Polymerase Chain Reaction) and phylogenetic tree analysis. Host range was tested by inoculating MYMIV using Bemisia tabaci to test plants. Two types of seeds were used in seed-borne tests, i.e. certified commercial seeds and malformed pods from infected plants. Results showed that yellow mosaic virus was found in all observation sites. Highest disease incidence was recorded in Sleman (50%) followed by Kulon Progo (45%) and Bantul (23%). Whereas 45.89%, 41.29% and 39.83%, disease severity was noted in Sleman, Kulon Progo and Bantul, respectively phylogenetic tree analysis showed that isolates used in this study were similar to other Indonesian isolates. Host range test revealed that yardlong beans, mungbeans (Vigna radiata L.), sesame seeds (Sesamum indicum L.), cucumber (Cucumis sativus L.), chili peppers (Capsicum annuum L.), eggplants (Solanum melongena L.), and tomatoes (Lycopersicum esculentum Mill.) were infected with MYMIV, showing symptoms of irregular yellow and mosaic spots on plant leaves. Transmission test exhibited that tobacco plant (Nicotiana tabacum L.) did not show viral infection. PCR detection proved that MYMIV isolates obtained from Yogyakarta may be transmitted through whole seeds, seed coat, cotyledon, and young leaves from sprouting seeds. Mild mosaic symptoms were appeared after sprouting, and gradually vein clearing was observed at 14 days, mosaic at 21 days, and complete leaf yellowing at 45 days after planting.
Keywords: Host range; Mungbean yellow mosaic india virus; Seed borne viruses; Vigna unguiculata sesquipedalis